Community Complexity Does Not Weaken Pairwise Coevolution in a Soil Bacterial Community - Zoltan Erdos; Daniel Padfield; Elze Hesse; Angus Buckling; Meaghan Castledine (Ecology Letters, 2025)
Exploitative interactions, such as predator–prey and host–parasite interactions, are ubiquitous in microbial communities. These interactions shape community density and composition, imposing strong selection on members to evolve countermeasures reducing the negative impacts of exploitation. Exploitative coevolution is often studied between species pairs in isolation, which may overestimate the strength and relevance of pairwise coevolution. Here we studied how community context influences coevolution between Pseudomonas fluorescens (exploited) and Variovorax sp. (exploiter). We evolved these species in pairwise coculture and embedded within a five‐species community to investigate evolved changes in pairwise interactions. We found evidence for asymmetrical coevolution: Variovorax evolved more rapidly than Pseudomonas , leading to increased exploitation through time, while Pseudomonas evolved increased tolerance to Variovorax with a time lag. The pairwise coevolutionary dynamics were not affected by the presence of other community members. Understanding how coevolutionary patterns change with increasing community complexity can have important implications for community persistence and function.

Rising Tide to Silent Tsunami: Unveiling the role of plastics in driving antimicrobial resistance - Emily M. Stevenson; Angus Buckling; Matthew Cole; Penelope K. Lindeque; Aimee K. Murray (Journal of Hazardous Materials, 2025)

Disturbances can facilitate prior invasions more than subsequent invasions in microbial communities - Luke Lear; Elze Hesse; Angus Buckling (Ecology Letters, 2024)
Invasions are commonly found to benefit from disturbance events. However, the importance of the relative timing of the invasion and disturbance for invader success and impact on community composition remains uncertain. Here, we experimentally test this by invading a five‐species bacterial community on eight separate occasions—four before a disturbance and four after. Invader success and impact on community composition was greatest when the invasion immediately followed the disturbance. However, the subsequent invasions had negligible success or impact. Pre‐disturbance, invader success and impact was greatest when the invader was added just before the disturbance. Importantly, however, the first three pre‐disturbance invasion events had significantly greater success than the last three post‐disturbance invasions. Moreover, these findings were consistent across a range of propagule pressures. Overall, we demonstrate that timing is highly important for both the success and impact on community composition of an invader, with both being lower as time since disturbance progresses.

Selection for antimicrobial resistance in the plastisphere - Emily M. Stevenson; Angus Buckling; Matthew Cole; Penelope K. Lindeque; Aimee K. Murray (Science of The Total Environment, 2024)

Diversity loss from multiple interacting disturbances is regime‐dependent - Luke Lear; Hidetoshi Inamine; Katriona Shea; Angus Buckling (Ecology Letters, 2023)
Anthropogenic activities expose many ecosystems to multiple novel disturbances simultaneously. Despite this, how biodiversity responds to simultaneous disturbances remains unclear, with conflicting empirical results on their interactive effects. Here, we experimentally test how one disturbance (an invasive species) affects the diversity of a community over multiple levels of another disturbance regime (pulse mortality). Specifically, we invade stably coexisting bacterial communities under four different pulse frequencies, and compare their final resident diversity to uninvaded communities under the same pulse mortality regimes. Our experiment shows that the disturbances synergistically interact, such that the invader significantly reduces resident diversity at high pulse frequency, but not at low. This work therefore highlights the need to study simultaneous disturbance effects over multiple disturbance regimes as well as to carefully document unmanipulated disturbances, and may help explain the conflicting results seen in previous multiple‐disturbance work.

Comparative experimental evolution reveals species‐specific idiosyncrasies in marine phytoplankton adaptation to warming - Samuel Barton; Daniel Padfield; Abigail Masterson; Angus Buckling; Nicholas Smirnoff; Gabriel Yvon‐Durocher (Global Change Biology, 2023)
A number of experimental studies have demonstrated that phytoplankton can display rapid thermal adaptation in response to warmed environments. While these studies provide insight into the evolutionary responses of single species, they tend to employ different experimental techniques. Consequently, our ability to compare the potential for thermal adaptation across different, ecologically relevant, species remains limited. Here, we address this limitation by conducting simultaneous long‐term warming experiments with the same experimental design on clonal isolates of three phylogenetically diverse species of marine phytoplankton; the cyanobacterium Synechococcus sp., the prasinophyte Ostreococcus tauri and the diatom Phaeodoactylum tricornutum . Over the same experimental time period, we observed differing levels of thermal adaptation in response to stressful supra‐optimal temperatures. Synechococcus sp. displayed the greatest improvement in fitness (i.e., growth rate) and thermal tolerance (i.e., temperature limits of growth). Ostreococcus tauri was able to improve fitness and thermal tolerance, but to a lesser extent. Finally, Phaeodoactylum tricornutum showed no signs of adaptation. These findings could help us understand how the structure of phytoplankton communities may change in response to warming, and possible biogeochemical implications, as some species show relatively more rapid adaptive shifts in their thermal tolerance.

Disturbance‐mediated invasions are dependent on community resource abundance - Luke Lear; Daniel Padfield; Hidetoshi Inamine; Katriona Shea; Angus Buckling (Ecology, 2022)
Disturbances can facilitate biological invasions, with the associated increase in resource availability being a proposed cause. Here, we experimentally tested the interactive effects of disturbance regime (different frequencies of biomass removal at equal intensities) and resource abundance on invasion success using a factorial design containing five disturbance frequencies and three resource levels. We invaded populations of the bacterium Pseudomonas fluorescens with two ecologically different invader morphotypes: a fast‐growing “colonizer” type and a slower growing “competitor” type. As resident populations were altered by the treatments, we additionally tested their effect on invader success. Disturbance frequency and resource abundance interacted to affect the success of both invaders, but this interaction differed between the invader types. The success of the colonizer type was positively affected by disturbance under high resources but negatively under low. However, disturbance negatively affected the success of the competitor type under high resource abundance but not under low or medium. Resident population changes did not alter invader success beyond direct treatment effects. We therefore demonstrate that the same disturbance regime can either be beneficial or detrimental for an invader depending on both community resource abundance and its life history. These results may help to explain some of the inconsistencies found in the disturbance‐invasion literature.

Stress causes interspecific facilitation within a compost community - Elze Hesse; Siobhan O'Brien; Adela M. Luján; Dirk Sanders; Florian Bayer; Eleanor M. van Veen; Dave J. Hodgson; Angus Buckling (Ecology Letters, 2021)
Ecological theory predicts interactions between species to become more positive under abiotic stress, while competition should prevail in more benign environments. However, experimental tests of this stress gradient hypothesis in natural microbial communities are lacking. We test this hypothesis by measuring interactions between 10 different members of a bacterial community inhabiting potting compost in the presence or absence of toxic copper stress. We found that copper stress caused significant net changes in species interaction signs, shifting the net balance towards more positive interactions. This pattern was at least in part driven by copper‐sensitive isolates – that produced relatively small amounts of metal‐detoxifying siderophores – benefitting from the presence of other species that produce extracellular detoxifying agents. As well as providing support for the stress gradient hypothesis, our results highlight the importance of community‐wide public goods in shaping microbial community composition.

How disturbance history alters invasion success: biotic legacies and regime change - Adam D. Miller; Hidetoshi Inamine; Angus Buckling; Stephen H. Roxburgh; Katriona Shea (Ecology Letters, 2021)
Disturbance is a key factor shaping ecological communities, but little is understood about how the effects of disturbance processes accumulate over time. When disturbance regimes change, historical processes may influence future community structure, for example, by altering invasibility compared to communities with stable regimes. Here, we use an annual plant model to investigate how the history of disturbance alters invasion success. In particular, we show how two communities can have different outcomes from species introduction, solely due to past differences in disturbance regimes that generated different biotic legacies. We demonstrate that historical differences can enhance or suppress the persistence of introduced species, and that biotic legacies generated by stable disturbance history decay over time, though legacies can persist for unexpectedly long durations. This establishes a formal theoretical foundation for disturbance legacies having profound effects on communities, and highlights the value of further research on the biotic legacies of disturbance.

Determining the prevalence, identity and possible origin of bacterial pathogens in soil - Jacopo Ferraresso; Benedict Lawton; Sion Bayliss; Samuel Sheppard; Barbara Cardazzo; Will Gaze; Angus Buckling; Michiel Vos (Environmental Microbiology, 2020)
Summary Soil biomes are vast, exceptionally diverse and crucial to the health of ecosystems and societies. Soils also contain an appreciable, but understudied, diversity of opportunistic human pathogens. With climate change and other forms of environmental degradation potentially increasing exposure risks to soilborne pathogens, it is necessary to gain a better understanding of their ecological drivers. Here we use the Galleria mellonella insect virulence model to selectively isolate pathogenic bacteria from soils in Cornwall (UK). We find a high prevalence of pathogenic soil bacteria with two genera, Providencia and Serratia, being especially common. Providencia alcalifaciens , P. rustigianii, Serratia liquefaciens and S. plymuthica strains were studied in more detail using phenotypic virulence and antibiotic resistance assays and whole‐genome sequencing. Both genera displayed low levels of antibiotic resistance and antibiotic resistance gene carriage. However, Serratia isolates were found to carry the recently characterized metallo‐β‐lactamase bla SPR‐1 that, although not conferring high levels of resistance in these strains, poses a potential risk of horizontal transfer to other pathogens where it could be fully functional. The Galleria assay can be a useful approach to uncover the distribution and identity of pathogenic bacteria in the environment, as well as uncover resistance genes with an environmental origin.

Experimental (co)evolution in a multi‐species microbial community results in local maladaptation - Meaghan Castledine; Daniel Padfield; Angus Buckling (Ecology Letters, 2020)
Interspecific coevolutionary interactions can result in rapid biotic adaptation, but most studies have focused only on species pairs. Here, we (co)evolved five microbial species in replicate polycultures and monocultures and quantified local adaptation. Specifically, growth rate assays were used to determine adaptations of each species’ populations to (1) the presence of the other four species in general and (2) sympatric vs . allopatric communities. We found that species did not show an increase in net biotic adaptation:ancestral, polyculture‐ and monoculture‐evolved populations did not have significantly different growth rates within communities. However, 4/5 species’ growth rates were significantly lower within the community they evolved in relative to an allopatric community. ‘Local maladaptation’ suggests that species evolved increased competitive interactions to sympatric species’ populations. This increased competition did not affect community stability or productivity. Our results suggest that (co)evolution within communities can increase competitive interactions that are specific to (co)evolved community members.

Evolutionary temperature compensation of carbon fixation in marine phytoplankton - Samuel Barton; James Jenkins; Angus Buckling; C.-Elisa Schaum; Nicholas Smirnoff; John A. Raven; Gabriel Yvon‐Durocher (Ecology Letters, 2020)
The efficiency of carbon sequestration by the biological pump could decline in the coming decades because respiration tends to increase more with temperature than photosynthesis. Despite these differences in the short‐term temperature sensitivities of photosynthesis and respiration, it remains unknown whether the long‐term impacts of global warming on metabolic rates of phytoplankton can be modulated by evolutionary adaptation. We found that respiration was consistently more temperature dependent than photosynthesis across 18 diverse marine phytoplankton, resulting in universal declines in the rate of carbon fixation with short‐term increases in temperature. Long‐term experimental evolution under high temperature reversed the short‐term stimulation of metabolic rates, resulting in increased rates of carbon fixation. Our findings suggest that thermal adaptation may therefore have an ameliorating impact on the efficiency of phytoplankton as primary mediators of the biological carbon pump.

Biodiversity–function relationships in methanogenic communities - Pawel Sierocinski; Florian Bayer; Gabriel Yvon‐Durocher; Melia Burdon; Tobias Großkopf; Mark Alston; David Swarbreck; Phil J. Hobbs; Orkun S. Soyer; Angus Buckling (Molecular Ecology, 2018)
Methanogenic communities play a crucial role in carbon cycling and biotechnology (anaerobic digestion), but our understanding of how their diversity, or composition in general, determines the rate of methane production is very limited. Studies to date have been correlational because of the difficulty in cultivating their constituent species in pure culture. Here, we investigate the causal link between methanogenesis and diversity in laboratory anaerobic digesters by experimentally manipulating the diversity of cultures by dilution and subsequent equilibration of biomass. This process necessarily leads to the loss of the rarer species from communities. We find a positive relationship between methane production and the number of taxa, with little evidence of functional saturation, suggesting that rare species play an important role in methane‐producing communities. No correlations were found between the initial composition and methane production across natural communities, but a positive relationship between species richness and methane production emerged following ecological selection imposed by the laboratory conditions. Our data suggest methanogenic communities show little functional redundancy, and hence, any loss of diversity—both natural and resulting from changes in propagation conditions during anaerobic digestion—is likely to reduce methane production.

Linking phytoplankton community metabolism to the individual size distribution - Daniel Padfield; Angus Buckling; Ruth Warfield; Chris Lowe; Gabriel Yvon‐Durocher (Ecology Letters, 2018)
Quantifying variation in ecosystem metabolism is critical to predicting the impacts of environmental change on the carbon cycle. We used a metabolic scaling framework to investigate how body size and temperature influence phytoplankton community metabolism. We tested this framework using phytoplankton sampled from an outdoor mesocosm experiment, where communities had been either experimentally warmed (+ 4 °C) for 10 years or left at ambient temperature. Warmed and ambient phytoplankton communities differed substantially in their taxonomic composition and size structure. Despite this, the response of primary production and community respiration to long‐ and short‐term warming could be estimated using a model that accounted for the size‐ and temperature dependence of individual metabolism, and the community abundance‐body size distribution. This work demonstrates that the key metabolic fluxes that determine the carbon balance of planktonic ecosystems can be approximated using metabolic scaling theory, with knowledge of the individual size distribution and environmental temperature.

Ecological selection of siderophore‐producing microbial taxa in response to heavy metal contamination - Elze Hesse; Siobhán O'Brien; Nicolas Tromas; Florian Bayer; Adela M. Luján; Eleanor M. van Veen; Dave J. Hodgson; Angus Buckling (Ecology Letters, 2018)
Some microbial public goods can provide both individual and community‐wide benefits, and are open to exploitation by non‐producing species. One such example is the production of metal‐detoxifying siderophores. Here, we investigate whether conflicting selection pressures on siderophore production by heavy metals – a detoxifying effect of siderophores, and exploitation of this detoxifying effect – result in a net increase or decrease. We show that the proportion of siderophore‐producing taxa increases along a natural heavy metal gradient. A causal link between metal contamination and siderophore production was subsequently demonstrated in a microcosm experiment in compost, in which we observed changes in community composition towards taxa that produce relatively more siderophores following copper contamination. We confirmed the selective benefit of siderophores by showing that taxa producing large amounts of siderophore suffered less growth inhibition in toxic copper. Our results suggest that ecological selection will favour siderophore‐mediated decontamination, with important consequences for potential remediation strategies.

Metabolic compensation constrains the temperature dependence of gross primary production - Daniel Padfield; Chris Lowe; Angus Buckling; Richard Ffrench‐Constant; Simon Jennings; Felicity Shelley; Jón S. Ólafsson; Gabriel Yvon‐Durocher (Ecology Letters, 2017)
Gross primary production ( GPP ) is the largest flux in the carbon cycle, yet its response to global warming is highly uncertain. The temperature dependence of GPP is directly linked to photosynthetic physiology, but the response of GPP to warming over longer timescales could also be shaped by ecological and evolutionary processes that drive variation in community structure and functional trait distributions. Here, we show that selection on photosynthetic traits within and across taxa dampens the effects of temperature on GPP across a catchment of geothermally heated streams. Autotrophs from cold streams had higher photosynthetic rates and after accounting for differences in biomass among sites, biomass‐specific GPP was independent of temperature in spite of a 20 °C thermal gradient. Our results suggest that temperature compensation of photosynthetic rates constrains the long‐term temperature dependence of GPP , and highlights the importance of considering physiological, ecological and evolutionary mechanisms when predicting how ecosystem‐level processes respond to warming.

Parasite genetic distance and local adaptation in co‐evolving bacteria–bacteriophage populations - Pauline D. Scanlan; Alex R. Hall; Angus Buckling (Molecular Ecology, 2017)
Antagonistic co‐evolution between hosts and parasites can lead to local adaptation ( LA ) such that parasite fitness is greatest in sympatric hosts (or vice versa). The magnitude of LA typically increases with geographical distance, which is assumed to be because genetic (and hence phenotypic) distance increases with geographical distance. Here, we explicitly test the relationships between parasite genetic and phenotypic distance and LA using isolates of co‐evolved viral parasites (lytic bacteriophage ϕ2) and the host bacterium Pseudomonas fluorescens SBW 25. We find positive relationships between parasite genotype and infectivity phenotype, but the strength of the relationship was greater when infectivity was defined by the identity of hosts that could be infected rather than the actual number of hosts infected (host range), and when measurements were compared within rather than among populations. Crucially, we find a monotonic relationship between LA and genetic distance across phage isolates from different populations, although in contrast to many geographical studies, parasite LA decreased with genetic distance. These results can be explained by the fact that bacteria can rapidly adapt to phage infectivity mutations, but that evolved resistance has a degree of specificity to the local phage population. Our results show that antagonistic co‐evolution alone can result in predictable links between genetic distance and host–parasite local adaptation.

Host diversity limits the evolution of parasite local adaptation - Daniel Morley; Jenny M. Broniewski; Edze R. Westra; Angus Buckling; Stineke van Houte (Molecular Ecology, 2017)
Specificity in the interactions between hosts and their parasites can lead to local adaptation. However, the degree of local adaptation is predicted to depend upon the diversity of resistance alleles within the host population; increasing host diversity should decrease mean parasite infectivity and hence reduce local adaptation. In this study, we empirically test this prediction using the highly specific interactions between bacteria with clustered regularly interspaced short palindromic repeats/CRISPR‐associated (CRISPR/Cas) immunity and their bacteriophage. Bacteria acquire immunity to phage by incorporating a phage‐derived spacer sequence into CRISPR loci on the host genome, and phage can escape the CRISPR ‐mediated immunity of a specific clone by mutating the targeted sequence. We found that high levels of CRISPR allele diversity that naturally evolve in host populations exposed to phage (because each bacterial clone captures a unique phage‐derived sequence) prevents phage from becoming locally adapted. By manipulating the number of CRISPR alleles in the host population, we show that phage can become locally adapted to their bacterial hosts but only when CRISPR allele diversity is low.

Migration highways and migration barriers created by host–parasite interactions - Quan‐Guo Zhang; Angus Buckling (Ecology Letters, 2016)
Co‐evolving parasites may play a key role in host migration and population structure. Using co‐evolving bacteria and viruses, we test general hypotheses as to how co‐evolving parasites affect the success of passive host migration between habitats that can support different intensities of host–parasite interactions. First, we show that parasites aid migration from areas of intense to weak co‐evolutionary interactions and impede migration in the opposite direction, as a result of intraspecific apparent competition mediated via parasites. Second, when habitats show qualitative difference such that some environments support parasite persistence while others do not, different population regulation forces (either parasitism or competitive exclusion) will reduce the success of migration in both directions. Our study shows that co‐evolution with parasites can predictably homogenises or isolates host populations, depending on heterogeneity of abiotic conditions, with the second scenario constituting a novel type of ‘isolation by adaptation’.

Resource‐dependent antagonistic coevolution leads to a new paradox of enrichment - Quan‐Guo Zhang; Angus Buckling (Ecology, 2016)
The classical, ecological, paradox of enrichment describes a phenomenon that resource enrichment destabilizes predator–prey systems by exacerbating population oscillations. Here we suggest a new, evolutionary, paradox of enrichment. Resource enrichment can lead to more asymmetrical predator–prey coevolution (i.e., extremely high levels of prey defenses against predators) that decreases predator abundances and increases predator extinction risk. A major reason for this is that high resource availability can reduce fitness costs associated with prey defenses. In our experiments with a bacterium and its lytic phage, nutrient‐balanced resource enrichment led to patterns in population demography and coevolutionary dynamics consistent with this coevolution‐based paradox of enrichment; in particular, phage population extinction events were observed under nutrient‐rich, not nutrient‐poor, conditions. Consistent with ecological studies, carbon‐biased resource enrichment (with carbon availability disproportionately increased relative to other nutrients) did not destabilize dynamics, and the asymmetry of coevolution was not altered in this context. Our work highlights the importance of integrating ecological and evolutionary thinking for studies of the consequences of nutrient pollution and other types of environmental changes.

Rapid evolution of metabolic traits explains thermal adaptation in phytoplankton - Daniel Padfield; Genevieve Yvon‐Durocher; Angus Buckling; Simon Jennings; Gabriel Yvon‐Durocher (Ecology Letters, 2016)
Understanding the mechanisms that determine how phytoplankton adapt to warming will substantially improve the realism of models describing ecological and biogeochemical effects of climate change. Here, we quantify the evolution of elevated thermal tolerance in the phytoplankton, Chlorella vulgaris . Initially, population growth was limited at higher temperatures because respiration was more sensitive to temperature than photosynthesis meaning less carbon was available for growth. Tolerance to high temperature evolved after ≈ 100 generations via greater down‐regulation of respiration relative to photosynthesis. By down‐regulating respiration, phytoplankton overcame the metabolic constraint imposed by the greater temperature sensitivity of respiration and more efficiently allocated fixed carbon to growth. Rapid evolution of carbon‐use efficiency provides a potentially general mechanism for thermal adaptation in phytoplankton and implies that evolutionary responses in phytoplankton will modify biogeochemical cycles and hence food web structure and function under warming. Models of climate futures that ignore adaptation would usefully be revisited.

Quality and Safety Requirements for Sustainable Phage Therapy Products - Jean-Paul Pirnay; Bob G. Blasdel; Laurent Bretaudeau; Angus Buckling; Nina Chanishvili; Jason R. Clark; Sofia Corte-Real; Laurent Debarbieux; Alain Dublanchet; Daniel De Vos; Jérôme Gabard; Miguel Garcia; et al. (Pharmaceutical Research, 2015)

Higher resources decrease fluctuating selection during host–parasite coevolution - Laura Lopez Pascua; Alex R. Hall; Alex Best; Andrew D. Morgan; Mike Boots; Angus Buckling (Ecology Letters, 2014)
We still know very little about how the environment influences coevolutionary dynamics. Here, we investigated both theoretically and empirically how nutrient availability affects the relative extent of escalation of resistance and infectivity (arms race dynamic; ARD ) and fluctuating selection (fluctuating selection dynamic; FSD ) in experimentally coevolving populations of bacteria and viruses. By comparing interactions between clones of bacteria and viruses both within‐ and between‐time points, we show that increasing nutrient availability resulted in coevolution shifting from FSD , with fluctuations in average infectivity and resistance ranges over time, to ARD . Our model shows that range fluctuations with lower nutrient availability can be explained both by elevated costs of resistance (a direct effect of nutrient availability), and reduced benefits of resistance when population sizes of hosts and parasites are lower (an indirect effect). Nutrient availability can therefore predictably and generally affect qualitative coevolutionary dynamics by both direct and indirect (mediated through ecological feedbacks) effects on costs of resistance.

Real‐time microbial adaptive diversification in soil - Pedro Gómez; Angus Buckling (Ecology Letters, 2013)
Bacteria undergo adaptive diversification over a matter of days in test tubes, but the relevance to natural populations remains unclear. Here, we report real‐time adaptive diversification of the bacterium Pseudomonas fluorescens in its natural environment, soil. Crucially, adaptive diversification was much greater in the absence of the established natural microbial community, suggesting that resident diversity is likely to inhibit, rather than promote, adaptive radiations in natural environments. Rapid diversification is therefore likely to play an important role in the population and community dynamics of microbes in environments where resident communities are perturbed, such as by agriculture, pollution and antibiotics.

Effects of predation on real‐time host–parasite coevolutionary dynamics - Ville‐Petri Friman; Angus Buckling (Ecology Letters, 2013)
The impact of community complexity on pairwise coevolutionary dynamics is theoretically dependent on the extent to which species evolve generalised or specialised adaptations to the multiple species they interact with. Here, we show that the bacteria Pseudomonas fluorescens diversifies into defence specialists, when coevolved simultaneously with a virus and a predatory protist, as a result of fitness trade‐offs between defences against the two enemies. Strong bacteria–virus pairwise coevolution persisted, despite strong protist‐imposed selection. However, the arms race dynamic (escalation of host resistance and parasite infectivity ranges) associated with bacteria–virus coevolution broke down to a greater extent in the presence of the protist, presumably through the elevated genetic and demographic costs of increased bacteria resistance ranges. These findings suggest that strong pairwise coevolution can persist even in complex communities, when conflicting selection leads to evolutionary diversification of different defence strategies.

Selection on non‐social traits limits the invasion of social cheats - Andrew D. Morgan; Benjamin J. Z. Quigley; Sam P. Brown; Angus Buckling (Ecology Letters, 2012)
While the conditions that favour the maintenance of cooperation have been extensively investigated, the significance of non‐social selection pressures on social behaviours has received little attention. In the absence of non‐social selection pressures, patches of cooperators are vulnerable to invasion by cheats. However, we show both theoretically, and experimentally with the bacterium Pseudomonas fluorescens , that cheats may be unable to invade patches of cooperators under strong non‐social selection (both a novel abiotic environment and to a lesser extent, the presence of a virulent parasite). This is because beneficial mutations are most likely to arise in the numerically dominant cooperator population. Given the ubiquity of novel selection pressures on microbes, these results may help to explain why cooperation is the norm in natural populations of microbes.

The Phage Therapy Paradigm: Prêt-à-Porter or Sur-mesure? - Jean-Paul Pirnay; Daniel De Vos; Gilbert Verbeken; Maia Merabishvili; Nina Chanishvili; Mario Vaneechoutte; Martin Zizi; Geert Laire; Rob Lavigne; Isabelle Huys; Guy Van den Mooter; Angus Buckling; et al. (Pharmaceutical Research, 2011)

Genetic basis of infectivity evolution in a bacteriophage - PAULINE D. SCANLAN; ALEX R. HALL; LAURA D. C. LOPEZ‐PASCUA; ANGUS BUCKLING (Molecular Ecology, 2011)
Antagonistic coevolution between hosts and parasites is probably ubiquitous. However, very little is known of the genetic changes associated with parasite infectivity evolution during adaptation to a coevolving host. We followed the phenotypic and genetic changes in a lytic virus population (bacteriophage; phage Φ2) that coevolved with its bacterial host, Pseudomonas fluorescens SBW25. First, we show the rapid evolution of numerous unique phage infectivity phenotypes, and that both phage host range and bacterial resistance to individual phage increased over coevolutionary time. Second, each of the distinct phage phenotypes in our study had a unique genotype, and molecular evolution did not act uniformly across the phage genome during coevolution. In particular, we detected numerous substitutions on the tail fibre gene, which is involved in the first step of the host–parasite interaction: host adsorption. None of the observed mutations could be directly linked with infection against a particular host, suggesting that the phenotypic effects of infectivity mutations are probably epistatic. However, phage genotypes with the broadest host ranges had the largest number of nonsynonymous amino acid changes on genes implicated in infectivity evolution. An understanding of the molecular genetics of phage infectivity has helped to explain the complex phenotypic coevolutionary dynamics in this system.

Ecological drivers of the evolution of public‐goods cooperation in bacteria - Michael A. Brockhurst; Michelle G. J. L. Habets; Ben Libberton; Angus Buckling; Andy Gardner (Ecology, 2010)
The role of ecological processes in the evolution of social traits is increasingly recognized. Here, we explore, using a general theoretical model and experiments with bacteria, the joint effects of disturbance frequency and resource supply on the evolution of cooperative biofilm formation. Our results demonstrate that cooperation tends to peak at intermediate frequencies of disturbance but that the peak shifts toward progressively higher frequencies of disturbance as resource supply increases. This appears to arise due to increased growth rates at higher levels of resource supply, which allows cooperators to more rapidly exceed the density threshold above which cooperation is beneficial following catastrophic disturbance. These findings demonstrate for the first time the importance of interactions between ecological processes in the evolution of public‐goods cooperation and suggest that cooperation can be favored by selection across a wide range of ecological conditions.

Parasites mediate the relationship between host diversity and disturbance frequency - Andrew D. Morgan; Angus Buckling (Ecology Letters, 2004)
Patterns of community and population diversity are likely to be dependent on interactions between ecological variables. Here we address how two important ecological variables – extrinsic periodic mortality events (disturbances) and the presence of obligate‐killing parasites – interact to affect the diversity of niche‐specialist genotypes in laboratory populations of the bacterium Pseudomonas fluorescens . Consistent with previous studies, diversity was maximized at intermediate frequencies of disturbance in the absence of parasitic bacteriophages (phages). By contrast, no relationship was found between diversity and disturbance frequency in the presence of phage. The results can be explained in part by differential effects of phage on bacterial densities, and hence resource competition, under different disturbance regimes.

Population mixing accelerates coevolution - Michael A. Brockhurst; Andrew D. Morgan; Paul B. Rainey; Angus Buckling (Ecology Letters, 2003)
Theory predicts that mixing in spatially structured populations of hosts and parasites can increase the rate of antagonistic coevolution. We experimentally tested this prediction by allowing populations of bacteria ( Pseudomonas fluorescens ) and parasitic bacteriophage to coevolve in mixed and unmixed microcosms. Coevolution proceeded at approximately twice the rate in mixed populations compared with unmixed populations and caused the evolution of more resistant hosts and more infective parasites.